2022
DOI: 10.3389/fphar.2022.964037
|View full text |Cite
|
Sign up to set email alerts
|

Using an untargeted metabolomics approach to analyze serum metabolites in COVID-19 patients with nucleic acid turning negative

Abstract: Background: The coronavirus disease of 2019 (COVID-19) is a severe public health issue that has infected millions of people. The effective prevention and control of COVID-19 has resulted in a considerable increase in the number of cured cases. However, little research has been done on a complete metabonomic examination of metabolic alterations in COVID-19 patients following treatment. The current project pursues rigorously to characterize the variation of serum metabolites between healthy controls and COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our group has reported alteration in the levels of acylcarnitines and glycerophospholipids (phosphatidylcholines and lysophosphatidylcholines) upon admission in emergency rooms (early onset of symptoms) (López-Hernández et al, 2021). Chen and cols (Chen et al, 2022). reported that in COVID-19 patients with nucleic acid turning negative (still hospitalized), lipid metabolism was dysregulated.…”
Section: Discussionmentioning
confidence: 98%
“…Our group has reported alteration in the levels of acylcarnitines and glycerophospholipids (phosphatidylcholines and lysophosphatidylcholines) upon admission in emergency rooms (early onset of symptoms) (López-Hernández et al, 2021). Chen and cols (Chen et al, 2022). reported that in COVID-19 patients with nucleic acid turning negative (still hospitalized), lipid metabolism was dysregulated.…”
Section: Discussionmentioning
confidence: 98%
“…Y. López-Hernández showed early-stage alterations in acylcarnitines and glycerophospholipids (PCs and LPCs) in patients admitted to emergency rooms ( 136 ). Chen and colleagues have reported that even in patients with negative nucleic acid tests (still hospitalized), lipid metabolism remains dysregulated ( 137 ). Approximately two months post-discharge, Acosta-Ampudia et al.…”
Section: The Cain Triangle: Lipid Composition Alterations As An Indis...mentioning
confidence: 99%
“…Glutamate alteration in COVID-19 is in part mediated by the α-glutathione S-transferase, associated with certain processes such as liver failure, skeletal muscle metabolism, cancer or immunodeficiency ( Kinscherf et al, 1996 ; Cruzat et al, 2018 ). Other found alterations include the circulating exosome ( Alzahrani et al, 2021 ; Lam et al, 2021 ), the serum fatty acids ( Chen et al, 2022 ) and other serum lipids such as carnitines ( Castañé et al, 2022 ), ceramides ( Dei Cas et al, 2021 ; Khodadoust, 2021 ) and phospholipids ( Barberis et al, 2020 ; Shen et al, 2020 ; Janneh et al, 2021 ; Masoodi et al, 2022 ). The serum lipoprotein composition is also largely dysregulated ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ; Lodge et al, 2021c ; 2021a ; Gray et al, 2021 ; Masuda et al, 2021 ), showing a pathogenic redistribution of the lipoprotein particle size and composition to increase the atherosclerotic risk.…”
Section: Metabolic Signature Of the Acute Phase Of Sars-cov-2 Infectionmentioning
confidence: 99%